2019
DOI: 10.4191/kcers.2019.56.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Effective Oxygen-Defect Passivation in ZnO Thin Films Prepared by Atomic Layer Deposition Using Hydrogen Peroxide

Abstract: The intrinsic oxygen-vacancy defects in ZnO have prevented the preparation of p-type ZnO with high carrier concentration. Therefore, in this work, the effect of the concentration of H 2 O 2 (used as an oxygen source) on the oxygen-vacancy concentration in ZnO prepared by atomic layer deposition was investigated. The results indicated that the oxygen-vacancy concentration in the ZnO film decreased by the oxygen-rich growth conditions when using H 2 O 2 as the oxygen precursor instead of a conventional oxygen so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…As can be seen, the I (100)/ I (002) ratio shows a slight trend to decrease as the annealing temperature increases, suggesting the increase in the (002) preferential orientation of the ZnO films with the annealing temperature. According to the literature the latter trend results from the increase of anionic vacancies (oxygen vacancies) due to the poor-oxygen condition [36]. It seems to be consistent with that reported by Abdallah et al, who showed that an oxygen-rich environment promotes the non-polar (100) preferred orientation at the expense of the polar (002) orientation [37].…”
Section: Structural Characterizationsupporting
confidence: 88%
“…As can be seen, the I (100)/ I (002) ratio shows a slight trend to decrease as the annealing temperature increases, suggesting the increase in the (002) preferential orientation of the ZnO films with the annealing temperature. According to the literature the latter trend results from the increase of anionic vacancies (oxygen vacancies) due to the poor-oxygen condition [36]. It seems to be consistent with that reported by Abdallah et al, who showed that an oxygen-rich environment promotes the non-polar (100) preferred orientation at the expense of the polar (002) orientation [37].…”
Section: Structural Characterizationsupporting
confidence: 88%
“…Please note that the ZnO films exhibit the typical polycrystalline structure, which was mainly oriented to the (002) direction (34.50°) as in Figure S1a . For the wurtzite-structure ZnO, the c-axis (002) plane has been known as the most densely packed and thermodynamically stable orientation [ 29 , 30 ]. We conducted the XRD analysis of the ZnO film using the stacked structure as in the inset of Figure S1 , because of the penetration depth.…”
Section: Resultsmentioning
confidence: 99%